Effect of Azotobacter on Growth and Yield of Maize (SAARC Journal of Agriculture, 2014)
A field experiment was conducted to study the effect of Azotobacter on growth and yield of maize (variety Rampur composite) at farmland of National Maize Research Program, Rampur, Chitwan, Nepal during the winter season of 2007-08 and 2008-09. The experiment was laid out in randomized complete block design with eight treatments each replicated three times. The treatments were control, 120:60:40 kg NP2O5K2O ha-1, Azotobacter seed inoculation, Azotobacter soil application, Azotobacter +10 t FYM ha-1, 10 t FYM ha-1, 120:60:40 kg NP2O5K2O ha-1 + Azotobacter, 120:60:40 kg NP2O5K2O ha-1 + Azotobacter + 10 t FYM ha-1. Analysis of variance showed that grain yield, plant height, ear height, ear length, kernel per rows and 1000 grain weight were significantly affected with treatments. Only inoculation of Azotobacter increased 15 to 35% grain yield over non inoculated treatments. The benefit of Azotobacter inoculation was higher in the absence of chemical fertilizer application. DOI: http://dx.doi.org/10.3329/sja.v11i2.18409 SAARC J. Agri., 11(2): 141-147 (2013)